The recovery programme for the Regent honeyeater Anthochaera phrygia: an example of conservation collaboration in Australia. Issue 1 (18th December 2013) - Liu, S. C.; Gillespie, J.; Atchison, N.; Andrew, P.
<x xml:space="preserve">Abstract</x> The Regent honeyeater Anthochaera phrygia is a Critically Endangered meliphagid endemic to the temperate forests of south‐eastern Australia. The species has been the subject of a national recovery effort for the past two decades. Recovery has evolved into a collaboration involving zoo professionals, wildlife agencies, non‐government organizations and local communities. This paper describes the zoo component of the recovery effort, from preparatory work on analogue species through to the release of captive‐bred birds from the regionally managed zoo population. Husbandry and breeding techniques, acclimatization and release protocols, and institutional involvement in broader community awareness are described. Key to the progress made to date has been a functional and representative Recovery Team, the allocation of each task (along with responsibility for both implementation and funding) to the most appropriate organization, and an evolving strategy that has responded quickly to perceived needs and achievable goals.